Shaping the Future: Strategy Making as Artificial Evolution - Patvardhan, Shubha; Ramachandran, J. (Organization Science, 2020)
To investigate how firms engage in forward-looking action, we examined the processes by which a pioneering firm actively influenced the future of its industry over five decades. From our longitudinal field study, we generated a process model of strategy making that helps to explain how firms work to shape the future in some preferred fashion. Specifically, we describe our findings on shaping-oriented forward-looking strategy making in terms of “artificial evolution” processes—interventions by which a firm’s leaders challenge the status quo and leverage the internal ecology of the organization to nudge the evolution of the business landscape toward a preferred direction. This is distinct from the more conventional and commonly invoked natural selection processes that describe how firms adapt to markets or unintentionally shape them. These findings on strategy making as akin to artificial evolution complement and extend the traditional view of strategic management, which has historically focused on processes anchored in models of search and adaptation. Our findings also shed light on an exceptional mode of strategy making—one that goes beyond concerns of firm survival and competitive advantage, and tackles societal grand challenges. By accounting for constructivist, forward-looking dimensions of strategic agency, our findings also contribute to the microfoundations of strategic decision making and to organization theories, more generally.